Denial Syndrome di Masa Pandemi Covid-19 pada Masyarakat Kabupaten Pamekasan Madura - Iswatun Hasanah; Imaniyatul Fitriyah; Septinda Rima Dewanti; Sri Rizqi Wahyuningrum (Institut Agama Islam Neegri Madura, 2021)
The Covid-19 pandemic in Pamekasan Regency has had a major impact on various aspects of people's lives, especially in terms of health, namely Covid-19 can cause respiratory system disorders, severe lung infections, and even death. The frightening condition of the Covid-19 Pandemic can lead to denial and denial of the truth (Denial Syndrome). Denial Syndrome is a form of self-defense against anxiety against a threatening reality. In the short term Denial Syndrome will help individuals to think logically and make peace with their own fears, but in the long term Denial Syndrome will be dangerous and cause problems for themselves or the environment. Empirical phenomenological research through observations and interviews regarding the behavior of the Pamekasan community in dealing with the Covid-19 pandemic shows a prolonged Denial Syndrome, so that the impact is the spread of the virus quickly and widely which results in the number of cases being positively infected with the corona virus and the death increasing. Therefore, every individual must be able to accept and be aware of the existence of the corona virus and its impact on themselves and others by making various efforts so that they can continue to carry out routines without conflicting with government regulations. This can be a solution for individuals to get out of their comfort zone and make peace with themselves and the situation so that this Pandemic can be resolved properly.